PENCATATAN PERSEDIAAN DAN PENETAPAN HARGA POKOK PERSEDIAAN PADA PT PERHUTANI (PERSERO) - Sitorus, Frangky Yosua; Siagian, Yunus Meherlin; Malau, Melinda (Universitas Kristen Indonesia, 2017)
Trading companies play a major role in world economic activity. Entry and exit of goods, raises revenues and expenditures of money occurred. If you do not want to lose market share in the competitive trade, is the basis for an accountant to be ready and have the initiative in practice what is learned during bench formal. Theory education complex and in practice in the world of work more flexible and easier to apply. But a lot of difference between theory and practice that companies use a method that is more simple, effective and efficient. Findings are compared later writers get into new things that can be learned. When seeing things that do not fit with the theory learned, became something new to the author learned as stock in later day. Of making the report job training, the author makes a conclusion that can find companies in the register and in determining the cost of inventory to the hands consumer.Kata kunci: Aset, Persediaan, Pembelian, Penjualan